Thermal stability and high-temperature behavior of the natural borate colemanite: An aggregate in radiation-shielding concretes. (10th April 2019) - Lotti, Paolo; Comboni, Davide; Gigli, Lara; Carlucci, Lucia; Mossini, Eros; Macerata, Elena; Mariani, Mario; Gatta, G. Diego
Graphical abstract: Highlights: Colemanite can be used as an aggregate in neutron radiation-shielding concretes. We have investigated its high- T behavior by means of DSC, TG and XRD analyses. The loss of structural H2 O unambiguously occurs at least from ∼240 °C. At T > 325 °C an irreversible amorphization towards an anhydrous form occurs. The amorphization process is triggered in the very early stages of dehydration. Abstract: Colemanite is a natural borate that can be used as an aggregate in neutron-radiation shielding concretes. In this study, we report its thermal behavior, up to 500 °C, by describing: 1) its dehydration mechanisms and 2) its thermo-elastic parameters. The thermal expansion of colemanite is significantly anisotropic. The refined volume thermal expansion coefficient at ambient conditions is: α V 0 = 4.50(10)·10 −5 K −1 . The loss of structural H2 O occurs at least from ∼240 °C, and at T > 325 °C an irreversible amorphization occurs, followed by a complete dehydration. The potential implications on the use of colemanite as concrete-aggregate are discussed.